Two methods to adapt the human haemoglobin–oxygen dissociation algorithm to the blood of white rhinoceros (Ceratotherium simum) and to determine the accuracy of pulse oximetry. (September 2016) - Haymerle, Agnes; Knauer, Felix; Walzer, Chris
Abstract: Objectives: To adapt the algorithm for the calculation of oxygen saturation to the blood characteristics of the white rhinoceros by two different methods and to determine the accuracy of conventional pulse oximetry measurements. Study design: Adaptation of two mathematical models of the oxygen dissociation curve (ODC). Animals: Twenty-five captive white rhinoceros ( Ceratotherium simum ), including 12 males and 13 females, aged 6–32 years. Methods: During 33 anaesthetic events, 94 arterial blood gas samples with 72 simultaneous pulse oximetry measurements were analysed. The calculation of oxygen saturation was adapted to the characteristics of rhinoceros blood using two different methods. Firstly, a mathematical model developed in 1984 and, secondly, an oxygen status algorithm (OSA) produced by the same developer in 2005 were tested for their applicability for clinical use. Results: When arterial partial pressure of oxygen is >7.98 kPa (60 mmHg), oxygen saturation exceeds 95%. At partial pressures of 6.12–6.52 kPa (46–49 mmHg) Method 1 determined oxygen saturations of 92.5–95.3% and Method 2 oxygen saturations of 90.2–91.6%. Both methods resulted in similar ODCs and accounted for the low p50 value of rhinoceros blood. Method 1 provided better adaptation in respect to the physiological parameters of the rhinoceros, especially with regard to the Bohr effect, than Method 2. Pulse oximetry was an unreliable method of monitoring arterial oxygen saturation during general anaesthesia in this species. Conclusion: Adapting the oxygen saturation algorithm to consider the left shift of the ODC provides a useful tool for monitoring oxygen status, especially as pulse oximetry is insufficiently accurate. Experimental determination of the complete Hill curve is required to further validate and optimize the algorithm for use in the white rhinoceros. Clinical relevance: The method will facilitate the accurate interpretation of oxygen saturation calculated by blood gas analysis in white rhinoceros.